RIPK1 Expression Associates With Inflammation in Early Atherosclerosis in Humans and Can Be Therapeutically Silenced to Reduce NF-κB Activation and Atherogenesis in Mice. Issue 2 (12th January 2021) - Karunakaran, Denuja; Nguyen, My-Anh; Geoffrion, Michele; Vreeken, Dianne; Lister, Zachary; Cheng, Henry S.; Otte, Nicola; Essebier, Patricia; Wyatt, Hailey; Kandiah, Joshua W.; Jung, Richard; Alenghat, Francis J.; et al.
Abstract : Background: Chronic activation of the innate immune system drives inflammation and contributes directly to atherosclerosis. We previously showed that macrophages in the atherogenic plaque undergo RIPK3 (receptor-interacting serine/threonine-protein kinase 3)-MLKL (mixed lineage kinase domain-like protein)–dependent programmed necroptosis in response to sterile ligands such as oxidized low-density lipoprotein and damage-associated molecular patterns and that necroptosis is active in advanced atherosclerotic plaques. Upstream of the RIPK3-MLKL necroptotic machinery lies RIPK1 (receptor-interacting serine/threonine-protein kinase 1), which acts as a master switch that controls whether the cell undergoes NF-κB (nuclear factor κ-light-chain-enhancer of activated B cells)–dependent inflammation, caspase-dependent apoptosis, or necroptosis in response to extracellular stimuli. We therefore set out to investigate the role of RIPK1 in the development of atherosclerosis, which is driven largely by NF-κB–dependent inflammation at early stages. We hypothesize that, unlike RIPK3 and MLKL, RIPK1 primarily drives NF-κB–dependent inflammation in early atherogenic lesions, and knocking down RIPK1 will reduce inflammatory cell activation and protect against the progression of atherosclerosis. Methods: We examined expression of RIPK1 protein and mRNA in both human and mouse atherosclerotic lesions, and used loss-of-function approaches in vitro in macrophages and endothelial cells to measure inflammatory responses. We administered weekly injections of RIPK1 antisense oligonucleotides to Apoe −/− mice fed a cholesterol-rich (Western) diet for 8 weeks. Results: We find that RIPK1 expression is abundant in early-stage atherosclerotic lesions in both humans and mice. Treatment with RIPK1 antisense oligonucleotides led to a reduction in aortic sinus and en face lesion areas (47.2% or 58.8% decrease relative to control, P <0.01) and plasma inflammatory cytokines (IL-1α [interleukin 1α], IL-17A [interleukin 17A], P <0.05) in comparison with controls. RIPK1 knockdown in macrophages decreased inflammatory genes (NF-κB, TNFα [tumor necrosis factor α], IL-1α) and in vivo lipopolysaccharide- and atherogenic diet–induced NF-κB activation. In endothelial cells, knockdown of RIPK1 prevented NF-κB translocation to the nucleus in response to TNFα, where accordingly there was a reduction in gene expression of IL1B, E-selectin, and monocyte attachment. Conclusions: We identify RIPK1 as a central driver of inflammation in atherosclerosis by its ability to activate the NF-κB pathway and promote inflammatory cytokine release. Given the high levels of RIPK1 expression in human atherosclerotic lesions, our study suggests RIPK1 as a future therapeutic target to reduce residual inflammation in patients at high risk of coronary artery disease. Abstract : Supplemental Digital Content is available in the text.